Temporal dynamics in functional fruit traits of native and invasive fleshy fruited plants in subtropical Andean forests - Bender, Irene Maria Antoinetta (2025)
1. Fruits encompass the energetic and material flow between both interacting parties in frugivore- mediated seed dispersal. Since fruit traits matter in frugivores' foraging decisions, the temporal dynamics of fruit traits might influence interaction outcomes. However, community phenological patterns that determine fruit trait availability can be altered by invasive non- native fleshy- fruited species (‘INNFS’), potentially disrupting native plant–animal interactions. 2. We aim to determine the relative contributions of native plants and INNFS to the temporal dynamics of ripe fruit variability in terms of abundance and morphological, and nutritional functional traits. Additionally, we test whether INNFS are morphologically and nutritionally redundant to the native fruiting community and whether the fruiting phenology of INNFS supplements variation in native fruit abundance throughout the year. 3. We surveyed ripe fruit abundance in 22 sites of a subtropical Andean forest in north- western Argentina and combined this with available data on morphological and nutritional traits for 52 native species and five INNFS. Multidimensional trait spaces were constructed and functional diversity metrics calculated for morphological and nutritional traits, weighted by species' fruit abundances. Data was grouped by time period (start of rainy season, end of rainy season and dry season) and groups were compared in terms of fruit abundance, (functional) diversity and turnover, and the differences between the native plant community and the complete plant community (i.e., including both native plants and INNFS) were explored. 4. The lowest amount of fruits, but highest species and functional diversity (morphological and nutritional), was available at the start of the rainy season. The highest fruit abundance occurred in the dry season, primarily due to INNFS, which were functionally redundant to native plant species. 5. Overall, INNFS do not functionally complement native fruit variation throughout the year. Due to their functional similarity to native fruits, INNFS might competitively affect natives, given that the foraging decisions of frugivores are guided primarily by the amount of fruit. We emphasize the importance of incorporating all phenological changes in fruiting phenology when discerning the effect of INNFS on native communities.